Corporate Social Responsibility-A Case Study of Balco Power Plant (Vedanta) - Lakra, Sunit; Kumar, Mahesh (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The Concept of CSR is slowly evolving with the development of India. The voluntary compliance of social and ecological responsibility of companies is called Corporate Social Responsibility. The Concept of CSR moves from philanthropy and charity to women empowerment & rural development and then to community development. Corporate social responsibility is the commitment of Organizations towards all stakeholders which includes employees, shareholders, investors, regulators, consumers and community. The main domain of CSR activities are employee welfare, women empowerment, social and economic development, community welfare and environmental issues.Corporate Social Responsibility is a management concept whereby companies integrate social and environmental concerns in their business operations and interactions with their stakeholders. CSR is generally understood as being the way through which a company achieves a balance of economic, environmental and social imperatives (âTriple-Bottom-Line- Approachâ), while at the same time addressing the expectations of shareholders and stakeholders. In this sense it is important to draw a distinction between CSR, which can be a strategic business management concept, and charity, sponsorships or philanthropy. Even though the latter can also make a valuable contribution to poverty reduction, will directly enhance the reputation of a company and strengthen its brand, the concept of CSR clearly goes beyond that. This paper highlights the concept of CSR and practices exhibited by Balco Power Plant.